B2B e-commerce marketplaces and MSMES: Evidence of global value chain facilitation? - Maxime Ladrière; Kathryn Lundquist; Qing Ye (World Trade Organization (WTO), 2022)
In theory, e-commerce marketplaces connect buyers and sellers, open trade opportunities, and reduce transaction costs thereby creating opportunities for more inclusive trade and even GVC participation, especially for micro, small and medium-sized enterprises (MSMEs). Further, there is some evidence that MSMEs are more likely to use e-commerce marketplaces than large firms given these websites reduce search frictions and transaction costs, which can be relatively more beneficial for smaller firms. This discussion paper explores non-traditional data to investigate whether e-commerce marketplaces may contribute to MSME GVC participation. By looking at the development of business-to-business (B2B) e-commerce marketplaces, the gross merchandise value (GMV) of regional e-commerce marketplaces, and MSMEs' overall participation in B2B e-commerce marketplaces, descriptive statistics are gathered that contributes to the overall discussion on this topic. This discussion paper also links B2B e-commerce marketplaces with GVC facilitation through a novel approach of cataloguing these platforms' merchandise and finds that on average, roughly one third of B2B e-commerce marketplace listings are intermediate goods.
Keywords: F13; L81; O30; 330; Micro; Small and Medium Sized Enterprise (MSME); SME; e-commerce; marketplaces; global value chains (GVC)